2014
DOI: 10.1007/s00701-014-2222-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the anterior and posterior approach for transfer of the spinal accessory nerve to the suprascapular nerve in late traumatic brachial plexus injuries

Abstract: Better results in terms of external arm rotation were obtained when spinal accessory-to-suprascapular nerve transfer was performed using the posterior approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…In this study, we have found SAN to SSN transfer to provide only modest improvement when evaluating all injury types. Forty‐one percent of patients achieved some degree of ER in the current study, which is comparable to other reports in patient samples with heterogenous brachial plexus injuries . Yet, only 33% of these patients achieved ER within a useful range of motion needed for activities of daily living, which is more likely the true marker of a successful outcome.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, we have found SAN to SSN transfer to provide only modest improvement when evaluating all injury types. Forty‐one percent of patients achieved some degree of ER in the current study, which is comparable to other reports in patient samples with heterogenous brachial plexus injuries . Yet, only 33% of these patients achieved ER within a useful range of motion needed for activities of daily living, which is more likely the true marker of a successful outcome.…”
Section: Discussionsupporting
confidence: 83%
“…In the pediatric BPI literature, restoration of ER is emphasized, while adult BPI reviews have reported primarily shoulder abduction data . Reports of infraspinatus function following the SAN to SSN nerve transfer are highly variable and often contradicting, ranging from 8% to 100% in UT injuries . The purpose of this study is to critically evaluate recovery of ER following the SAN transfer to the SSN and to determine the factors affecting outcomes.…”
mentioning
confidence: 99%
“…These patients made up 75% of all patients who did not reach functional recovery. 22 In the patient group reported by Souza et al 79 no one was operated on before 6 months, all due to late referrals. Dubuisson even reported an average referral time of 6.8 months after injury.…”
Section: Late Referralsmentioning
confidence: 98%
“…Among the studies that reported individual patientlevel data, timing of operation and motor outcome were collected. 5,6,20,24,35,[48][49][50]52,56,[61][62][63][64]66,74,76,77,79,80,82,90,[93][94][95] A total of 569 patients were described individually. Patients were categorized into 5 groups based on length of delay (0-3, 3-6, 6-9, 9-12, and > 12 months; Table 4): 27.4% of patients were operated on within 3 months and 65.5% of all patients were operated on within 6 months.…”
Section: Individual-level Patient Datamentioning
confidence: 99%
See 1 more Smart Citation